METRO BUS service as an alternative to light rail transit - Ibrahim, Ishak (1995)
This research is done to determine some possible factors and characteristics that can make METRO BUS as a competitive choice to LRT in the public transport industry. Improvement in quality of service, capacity and efficiency are some factors that can bring revolution into METRO BUS service. Some comparisons will be made between LRT and METRO BUS services when necessary during the study. At the end of this research, there will be some guidelines on how to improve METRO BUS service.